Study How Honey Bees Use Visual Landmarks, Such as Distinctive Objects or Landscape Features, to Navigate and Maintain Spatial Awareness during Foraging or Migration - Muhammad Umair Sardar; Habib Ur Rehman (Indus Journal of Bioscience Research, 2023)
Objectives: This study investigated how honey bees utilize visual landmarks, such as distinctive objects or landscape features, to navigate and maintain spatial awareness during foraging or migration. Methods: The research was conducted in a designated honey bee apiary or natural foraging habitat in Lakki Marwat, starting in April 2023. Visual landmarks were selected based on their visibility, permanence, and uniqueness. Continuous monitoring and experimental trials were conducted to assess the impact of landmark manipulation on honey bee behavior. Results: Honey bees exhibited significantly lower flight path deviations (average deviation distance: 2m, maximum deviation distance: 5m) when visual landmarks were present in their original, unaltered state. The alteration of landmarks resulted in increased flight path deviations (average deviation distance: 3m, maximum deviation distance: 7m), while complete removal of landmarks led to even greater deviations (average deviation distance: 4m, maximum deviation distance: 9m). The bees showed a preference for distinct objects as landmarks during foraging, spending more time (average visit duration: 25s) and traveling longer distances (average distance traveled: 50m) when these landmarks were present. Navigational performance was also affected by landmark manipulation, with the control group achieving a higher success rate (90%) compared to the landmark altered group (76%) and the landmark removed group (72%). Conclusion: These findings emphasize the importance of visual cues, particularly distinct objects, in honey bee navigation and provide insights for improving beekeeping practices and understanding honey bee behavior.